Characterization Of Fusarium Mangiferae And F. Proliferatum, And Management Of Mango Malformation Disease - Rodzali, Haslinda (2021)
Mango is one of the most favourable fruits by Malaysians. Malaysia produced at an estimated of a hundred and two kilo tonnes of mango yearly. However, the local market demand towards mango is very high. Thus, Malaysia still imports the fruits from other countries such as Thailand and Australia. The occurrence of mango malformation disease (MMD) has been a stumbling block to mango production. Mango malformation disease has been a well-known disease since 1891 in India and gradually spread to other mango growing countries including Malaysia. Since then, several species of Fusarium have been reported to cause this disease in other countries including Egypt and China. However, none was confirmed in Malaysia. The disease has caused malformation of the inflorescence and vegetative parts of the tree making it as one of the most destructive diseases to mango tree. The disease affected the fruit production, from less to no yield if the plant was severely infected as the malformed inflorescence did not produce fruits. This research focused to determine the causal agent of MMD and evaluated the effectiveness of fungicides and biological agent in controlling the disease. In Malaysia, several species of Fusarium have been isolated from infected samples (panicles, leaflets and flowers) such as F. mangiferae, F. proliferatum, and F. subglutinans, but their pathogenicity tests were not completed